Dīnāmīkiyyah al-‘Alāqah bayna al-Lughah al-‘Arabiyyah wa Huwiyyah al-Fard wa al-Binā` al-Ijtimā‘ī fī Siyāq al-Da‘wah al-Mu‘āṣirah - Isra Mardi; Izzuddin Musthafa; Ade Nandang (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2025)
The Arabic language plays a strategic role in shaping individual religious identity and the social fabric of Muslim communities, particularly within the context of contemporary da'wah practices. This study aims to analyze how Arabic functions both as a linguistic and ideological tool in negotiating personal identity and social relations within da'wah spaces, whether through digital or traditional media. Employing a critical sociolinguistic approach and a descriptive qualitative method, this research explores practices such as code-switching, linguistic register variation, and the adaptation of Arabic to various da'wah contexts, including traditional environments such as Salafi religious institutes and digital da'wah platforms. The findings reveal that Arabic not only serves as a symbol of Islamic religiosity but also performs a semantic function in defining religious authority, social hierarchy, and symbolic capital in contemporary da'wah discourse. In urban settings, Arabic emerges as a symbol of the globalization of Islam and ideological affiliation, whereas in rural contexts, it serves as a means of preserving traditional religious knowledge. The study concludes that context-based Arabic language instruction and the adoption of flexible linguistic strategies are essential to support effective and inclusive da'wah communication in contemporary Muslim societies.